Sistem Rekrutmen Karyawan di RSU Muhammadiyah Ponorogo - Katmiatin Katmiatin (Pusat riset dan Inovasi Nasional, 2025)
The employee recruitment system is a crucial aspect in maintaining the quality of human resources in healthcare institutions, particularly hospitals based on Islamic values. Muhammadiyah Ponorogo General Hospital, as a hospital based on Muhammadiyah principles, faces the challenge of ensuring that every employee is not only technically competent but also aligned with Islamic values ​​and culture. This study aims to describe the employee recruitment process, identify the challenges faced, and explore best practices implemented at Muhammadiyah Ponorogo General Hospital. The study used a qualitative approach with data collection through in-depth interviews with Human Resources Development (HRD) and relevant stakeholders, direct observation of the selection process, and internal document review. Data were analyzed thematically to discover patterns and deeper meanings within the recruitment process. The results show that recruitment is carried out through the stages of identifying workforce needs, administrative selection, written tests, in-depth interviews to assess technical competency and Islamic value alignment, and medical examinations. The main challenge is the limited number of candidates who meet the dual criteria of having both professional expertise and moral integrity in line with Muhammadiyah values. Furthermore, maintaining transparency and objectivity in the selection process is also a crucial concern. The findings of this study indicate that the success of the recruitment system at Muhammadiyah Ponorogo General Hospital (RSU Muhammadiyah Ponorogo) depends heavily on good coordination between HRD and management, as well as the need to strengthen the value-based selection process. This way, the hospital can produce a workforce that is not only professional but also capable of supporting the institution's vision and mission of providing superior and Islamic healthcare services.